The effect of compressive loading on the residual gas permeability of concrete. (30th August 2019) - Miah, Md Jihad; Kallel, Hatem; Carré, Hélène; Pimienta, Pierre; La Borderie, Christian
Highlights: Permeability is investigated on unloaded or preloaded during the heating process. Axial permeability of concrete decreases with increasing radial confining pressure. Axial permeability increases with increasing preheating under uniaxial loading. Radial permeability of concrete decreases with increasing uniaxial compressive loading. Permeability strongly depends on crack width and orientation, both influenced by axial compression or radial confinement. Abstract: Concrete permeability is related to pore connectivity and measures the flow rate of gases and liquids through the concrete under a pressure gradient. Information about concrete permeability - both in ordinary environmental conditions and after the exposure to high temperature - is, therefore, badly needed to better understand fluid transport in concrete, with specific reference to high temperature. In fact, permeability influences concrete spalling in fire by favoring pore-pressure build-ups during the heating process. In this research project, two different procedures are adopted to carry out permeability tests on concrete specimens either unloaded or preloaded during the heating process. The results show that concrete permeability strongly depends on crack width and orientation, both are affected by the axial compression or radial confinement.